Latest Advances in Central Analgesic Mechanism of Osteopathic Manipulative Treatment for Cervical Spondylosis - JIN Zikai, WANG Xu, SUN Kai, WANG Yanguo, SHI Bin, LUO Jie, ZHU Liguo, WEI Xu (Zhongguo quanke yixue, 2023)
Osteopathic manipulative treatment (OMT) is a popular treatment for cervical spondylosis, a common degenerative disease of the spine. It has proven to be effective in relieving the pain from cervical spondylosis, but the mechanism is not clear. The development of neuroimaging has made it possible to perform visualization analyses of the cerebral structure and function in patients with cervical spondylosis, made the theory of somatosensory cortical remodeling proposed from the central perspective a new hot spot in the research on pathogenesis of cervical spondylosis, and the exploration of different manipulation treatments for cervical spondylosis based on the central effect a new direction of research on OMT. We reviewed the latest advances in central analgesic mechanisms of OMT for cervical spondylosis, mainly involving modulating the activity of brain regions, changing the default mode network, and regulating sympathetic nerve function, and summarized that OMT may improve pain via the following paths: enhancing central gating and modulating sensory-motor integration processes, or enhancing the strength of connections between sensory cortex and prefrontal cortex (an important structure for performing executive functions) in the default mode network, accelerating local neural remodelling and weakening white matter fibre connections between negative memory and emotion-related areas, or modulating sympathetic function and restoring brain mechanisms in inhibiting pain and central sensitisation for analgesic effects. The brain regions, functional brain networks and various biomarkers and observable indicators related to pain activation summarised in this study provide directions for future research. Future applied and basic research is recommended to adopt a step-by-step design, pay attention to the diversity of the research population, use the multi-point observation technique to assess the mechanism of efficacy, and enrich the scientific essentials of OMT.